2013
DOI: 10.26719/2013.19.11.947
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Klebsiella pneumoniae carbapenemase-mediated resistance in K. pneumoniae isolates from Egypt

Abstract: The emergence and rapid spread of antibiotic-resistant Klebsiella pneumoniae isolates harbouring the bla KPC gene that encodes for carbapenemase production have complicated the management of patient infections. This study in a tertiary care hospital in Egypt used real-time PCR assay to test ertapenem-nonsusceptible isolates of K. pneumoniae for the presence of the bla KPC gene and compared the results with modified Hodge test. Antibiotic sensitivity was performed by standard methods, and interpreted following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
4
18
2
Order By: Relevance
“…In this context, there has been a significant increase in carbapenem resistance among K. pneumoniae isolates in Egypt during the last few years (from 13.9% to 44.4%)33233. K. pneumoniae isolates possess several mechanisms to evade the activity of carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there has been a significant increase in carbapenem resistance among K. pneumoniae isolates in Egypt during the last few years (from 13.9% to 44.4%)33233. K. pneumoniae isolates possess several mechanisms to evade the activity of carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“… Sonnevend et al (2015a) , two K. pneumoniae ST14 strains producing KPC-2 were first identified in the United Arab Emirates of the Arabian Peninsula. In Africa, several countries such as South Africa ( Brink et al, 2012 ), Algeria ( Bakour et al, 2015b ), and Egypt ( Metwally et al, 2013 ), have also isolated KPC-producing K. pneumoniae .…”
Section: The Epidemiology Genetic Context Treatment Options and Dementioning
confidence: 99%
“…In addition, in a study in Egypt, Metwally et al investigated 20 K. pneumoniae isolates for KPC production by MHT. The results were positive in 14 isolates (70%) (24) . These results show a fair agreement with the results of the current study.…”
Section: Imipenem+edtamentioning
confidence: 99%
“…In Italy, Mosca et al investigated 38 K. pneumoniae isolates and found that all of the isolates (100%) were positive for blaKPC gene detection (23) . In Egypt, Metwally et al investigated 20 K. pneumoniae isolates; 14 isolates of which (70%) were found positive for blaKPC gene detection (24) . In the present study, among the 35 K. pneumoniae isolates which gave positive results for both EDTA disc synergy test and MHT, 5 isolates (14.28%) were positive for detection of blaNDM by PCR.…”
Section: Imipenem+edtamentioning
confidence: 99%